Promoting the effectiveness of social economy organisations: a proposal based on identity management - Nunes, F. G. (2020)
In this article, we propose that social economy organisations (SEOs) can improve their effectiveness if their leaders create a strategy for the management of organisational identity, that is, if they get involved in identity work. After placing the mission at the core of the effectiveness of SEOs, we identified four main focuses of identity work that we see as fundamental to promote the performance of these organisations: a) identity as a lens and as a compass; b) identity as a resource; c) management of multiple identities; d) identity as source of identification. We end with the suggestion of SEOs leaders' development practices that, by emphasizing these four lines of identity work, take advantage of organisational identity, a valuable asset to be used by all those who place the collective benefit above all other earning income obtained through organised action.